A Case of Congenital Bronchial Atresia Initially Presenting with Hemoptysis - Aoki, Ryota; Awashima, Maiko; Kodama, Tatsuya; Ota, Shinichiro; Hamakawa, Yusuke; Suematsu, Ryohei; Tagami, Yoichi; Fujikura, Yuji; Kanoh, Soichiro; Kawana, Akihiko (The Journal of the Japan Society for Respiratory Endoscopy, 2020)
Background. Congenital bronchial atresia is a relatively rare disease thought to be due to vascular abnormalities during embryonic development. To our knowledge, there have been no reports of congenital bronchial atresia with hemoptysis at the onset and bronchial artery-pulmonary vein shunting. Case. A 41-year-old man with no known medical illness suddenly developed hemoptysis. Chest computed tomography (CT) showed a tumor shadow in the left S3 region with abnormal blood vessels and air trapping in the peripheral region. Bronchial angiography showed shunting with the left pulmonary vein. At bronchoscopy, the entrance to the left B3 was not identifiable, so we made a diagnosis of congenital bronchial atresia. Following treatment with a hemostatic agent and antibiotics, the liquid component of the tumor was discharged and the hemoptysis resolved. Contrast CT after treatment showed no abnormal blood vessels or shunting. Conclusion. This case of bronchial atresia had readily recognizable abnormal blood vessels and bronchial artery-pulmonary vein shunting seen on bronchial angiography, but these resolved after treatment. This is suggestive of the involvement of abnormal blood vessels and collateral ventilation pathways in the pathogenesis of congenital bronchial atresia.